Prolactin–Growth Factor Crosstalk Reduces Mammary Estrogen Responsiveness Despite Elevated ERα Expression - Arendt, Lisa M. (American Society for Investigative Pathology, 2009)
Most breast cancers that occur in women express estrogen receptor α (ERα). However, a large subset of these cancers either does not initially respond to anti-estrogen therapy or develops resistance to such treatment modalities. One postulated mechanism of this failure is signaling cross talk between hormones and local growth factors. To examine these complex interactions in vivo, we assessed the effects of estrogen on transforming growth factor α (TGFα)- and prolactin (PRL)-induced mammary tumorigenesis in transgenic mice. Both PRL and estrogen reduced the latency of TGFα-induced oncogenesis, resulting in tumors that were variably ERα-positive, but were progesterone receptor-negative. However, despite elevated ERα levels in NRL-PRL/TGFα glands, tumor latency was not reduced with increasing estrogen levels, nor increased after ovariectomy. Furthermore, PRL and TGFα in combination blocked the mitogenic effects of estrogen, dramatically reduced progesterone receptor levels, and diminished ERα down-regulation in response to circulating estrogen levels, in contrast to the other genotypes. Notably, however, ductal morphology remained responsive to estrogen, indicating that TGFα and PRL in combination can inhibit some, but not all, estrogenic signals. Both in vitro and in vivo, PRL and TGFα cooperatively enhanced Akt phosphorylation, which is associated with endocrine resistance in human disease. These findings provide insight into the interactions of PRL with growth factors during mammary oncogenesis and suggest combinatorial approaches that may result in improved therapeutic efficacy.